Functionalized Fiber-Based Strain Sensors: Pathway to Next-Generation Wearable Electronics - Liu, Zekun; Zhu, Tianxue; Wang, Junru; Zheng, Zijian; Li, Yi; Li, Jiashen; Lai, Yuekun (Nano-Micro Letters, 2022)
Wearable strain sensors are arousing increasing research interests in recent years on account of their potentials in motion detection, personal and public healthcare, future entertainment, man–machine interaction, artificial intelligence, and so forth. Much research has focused on fiber-based sensors due to the appealing performance of fibers, including processing flexibility, wearing comfortability, outstanding lifetime and serviceability, low-cost and large-scale capacity. Herein, we review the latest advances in functionalization and device fabrication of fiber materials toward applications in fiber-based wearable strain sensors. We describe the approaches for preparing conductive fibers such as spinning, surface modification, and structural transformation. We also introduce the fabrication and sensing mechanisms of state-of-the-art sensors and analyze their merits and demerits. The applications toward motion detection, healthcare, man–machine interaction, future entertainment, and multifunctional sensing are summarized with typical examples. We finally critically analyze tough challenges and future remarks of fiber-based strain sensors, aiming to implement them in real applications. Highlights: 1 General principles for fiber functionalization and strain sensor fabrication are briefly reviewed. 2 Future application potentials of wearable strain sensors are summarized and evaluated. 3 Challenges and perspectives of fiber-based wearable strain sensors are critically discussed.